ANALISIS JENIS, JUMLAH, DAN MUTU GIZI KONSUMSI SARAPAN ANAK INDONESIA - Fachruddin Perdana; Hardinsyah Hardinsyah (Food and Nutrition Society of Indonesia, 2013)
The objective of this study was to analyze type, amount, and nutritional quality of breakfast among Indonesian children aged 3—12 years old. Data used for this study was secondary data of Basic Health Survey 2010 (Riskesdas 2010). Data was collected from June until August 2010 by applying a cross sectional design. This study covered 33 provinces of Indonesia, with total 40,437 children consisted of 20,659 boys and 19,778 girls. The results of this study showed that ten major type of foods consumed during breakfast were rice, swamp cabbage, egg, fish, tempe, instant noodles, tofu, bread, chicken and biscuits; and five major type of beverages consumed during breakfast were drinking water, tea, milk, coffee, and syrup. The food consumed on average of more than 5 g a day during breakfast were rice, swamp cabbage, egg, fish, tempe, instant noodles; and the beverages consumed on average of more than 15 mL a day were water, tea, and milk. Only 10.6% of children breakfast met energy intake>30% RDA.